The 2022 FIFA world cup in Qatar: resident interests and attitudes - Ahmed Abdulrahman Al-Emadi (23771415) (2024)
This study examined residents’ attitudes towards the staging of the 2022 FIFA World Cup in Qatar and assess their interest and level of support or opposition to this mega sport event. Guided by the Social Exchange Theory (SET) and the Social Representation Theory (SRT), the study used a survey conducted in 2019, involving 2031 residents: 1017 Qataris and 1014 non-Qataris. T-test and ANOVA analyses were employed. Examination of the factors shaping residents’ attitudes towards and interest in Qatar’s hosting of the 2022 FIFA World Cup revealed strong and positive associations between respondents’ demographic characteristics and their interest. Significant relationships were identified between respondents’ gender, nationality and educational level and interest in the 2022 World Cup. Findings suggest directions for sports policy makers and sport event managers to improve strategic planning for hosting major sporting events. Future research can draw on this study’s findings for adaption to other contexts. Other Information Published in: Soccer & Society License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/14660970.2024.2384907